Atividade antibacteriana do extrato hidroalcoólico de Punica granatum Linn. sobre Staphylococcus spp. isolados de leite bovino - Moreira, Giovanna M.B.; Matsumoto, Leopoldo S.; Silva, Regildo M.G. [UNESP]; Domingues, Paulo Francisco [UNESP]; Mello-Peixoto, Erika C.T. (FapUNIFESP (SciELO), 2014)
Bovine mastitis is characterized by inflammation of the mammary gland, usually in response to bacterial infection, affecting qualitatively and quantitatively milk production. This study aimed to determine the antibacterial activity in vitro of the hydroalcoholic extract of the bark of the pomegranate on bacteria isolated from bovine milk. The colonies of Staphylococcus spp. were resuspended in 6 MacFarland scale and adjusted its concentration by UV visible spectrophotometry at a concentration of 106ml-1. The extracts were evaluated in quintuplicate in seven concentrations: from 4 up to 0.0625mg.mL-1. The sensitivity of microbial isolates was determined using the disk diffusion and the results that showed inhibition halos corresponding to values from 15mm were considered susceptible. The results were evaluated by ANOVA, Tukey test 5% using the SISVAR 5.3-DEX/UFLA. Additionally the extract was assessed as for the antioxidant activity, content of phenols and total flavonoids. The extract was diluted into seven concentrations: 25-1.000µg.mL-1, and evaluated in triplicate. The bacterial growth was inhibited starting from the concentration of 4 mg.mL-1 and antioxidant activity was observed from 50µg.mL-1, with values corresponding to 4.62% reaching the plateau of 64.90% at a concentration of 500µg.mL-1. In evaluating the radical scavenging activity, using the free radical DPPH, the extract demonstrated antioxidant activity (IC50%= 378.80µg/mL). However it has not been possible to correlate the antioxidant activity with the levels of phenols and flavonoids. Perhaps the presence of other substances alkaloids and tannins present in the extracts may have been responsible for the antioxidant activity found. It was concluded that the hydroalcoholic extract of Punica granatum Linn. has antimicrobial activity against Staphylococcus spp., demonstrating potential benefit for the control of bovine mastitis.

Mastite bovina é caraterizada por inflamação da glândula mamária, geralmente em resposta à infecção bacteriana, compromete quali-quantitativamente a produção leiteira. Este estudo objetivou verificar a atividade antibacteriana in vitro do extrato hidroalcoólico da casca da romã sobre bactérias isoladas de leite bovino. As colônias de Staphylococcus spp. foram ressuspendidas a escala 6 de MacFarland e ajustada a sua concentração por espectrofotometria UV visível na concentração de 10 mL-1. Os extratos foram avaliados em quintuplicata, em sete concentrações: de 4mg mL-1 até 0,0625 mg.mL-1. A sensibilidade dos isolados microbianos foi determinada utilizando o teste de difusão em disco e os resultados que apresentaram zonas de inibição correspondentes a valores a partir de 15 mm, foram considerados sensíveis. Os resultados foram avaliados pelo método ANOVA, teste de Tukey 5%, utilizando o SISVAR 5.3 -DEX/UFLA. Adicionalmente o extrato foi avaliado quanto à atividade antioxidante, teores de fenóis e flavonoides totais. Para tanto o extrato foi diluído em sete concentrações: de 25 a 1000µg.mL-1, e avaliado em triplicata. O crescimento bacteriano foi inibido a partir da concentração de 4mg.mL-1 e a ação antioxidante foi verificada a partir de 50µg.mL-1, com valores correspondentes a 4.62%, atingindo platô de 64,90% na concentração de 500µg.mL-1. Na avaliação da atividade captadora de radicais, empregando o radical livre DPPH, o extrato demonstrou atividade antioxidante (IC50%= 378,80µg/mL). Porém, não foi possível correlacionar a atividade antioxidante aos teores de fenóis e flavonoides. Talvez a presença de outras substâncias alcaloides e taninos presentes no extrato, possam ter sido as responsáveis pela atividade antioxidante encontrada. Conclui-se que o extrato hidroalcoólico de Punica granatum Linn. apresenta atividade antimicrobiana contra Staphylococcus spp., demonstrando potencial benefício para o controle da mastite bovina.
Antibacterial activity of the hydroalcoholic extract of Punica granatum Linn. on Staphylococcus spp. isolated from bovine milk
Keywords: Mastitis; Antimicrobial; Natural extract; Medicinal plants; Organic production; Pomegranate; Mastite; Antimicrobiano; Extrato natural; Plantas Medicinais; Produção Orgânica; Romã